Safeguarding human rights: An indispensable component of the COVID-19 emergency response - Saurabh RamBihariLal Shrivastava (Indian Journal of Social Psychiatry, 2021)
In the ongoing battle against the Corona Virus Disease-2019 (COVID-19) pandemic, it is very important that the national leaders and health authorities must take appropriate measures to maintain an equilibrium between safeguarding the health, minimizing socioeconomic disruption, and protecting human rights of all the sections of the community. It is really a sad fact that the people who have been infected with the novel infection have been subjected to stigma and discrimination. As many nations have resorted to restriction of movements of the citizens, the girls and women are the most affected as their sexual and reproductive health needs are not being met, and in other words, these restrictions have aided in the violation of their human rights. In conclusion, the political leaders should understand the gravity of the situation and ensure that the human rights of all the sections of the society are given due importance by means of adoption of a comprehensive approach. In fact, safeguarding the human rights of the people is an important domain of the emergency public health response, and we all should not encourage discrimination of any kind against anyone.